Interpretasi Makna Lagu "Jalan Pulang" Karya Yura Yunita bagi Mahasiswa Rantau - Wahidin, Ahdi; Mayasari, Mayasari; Nayiroh, Luluatu (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study explores the meaning of Yura Yunita’s song “Jalan Pulang” for out-of-town students. The primary objective is to understand how this song resonates with students who are studying far from home. The research employs a qualitative method with an Alfred Schutz phenomenological approach, involving in-depth interviews, observations, and literature studies. Data were collected from three informants who are Communication Science students at Singaperbangsa University, Karawang. The findings reveal that the song serves as a source of encouragement, a reminder of home, and a means of emotional expression. Each student interprets the song based on their personal experiences, highlighting the diverse meanings attributed to “Jalan Pulang.” These interpretations range from seeing the song as a motivational tool to viewing it as a form of emotional solace. This study concludes that “Jalan Pulang” plays a significant role in alleviating homesickness, enhancing emotional well-being, and providing psychological support to out-of-town students. The diverse interpretations underscore the song's powerful impact in helping students navigate the emotional challenges of studying far from their families.